2011
DOI: 10.5005/jp-journals-10006-1133
|View full text |Cite
|
Sign up to set email alerts
|

Anemia during Pregnancy: Most Preventable yet most Prevalent

Abstract: Objective To study the relationship between maternal hemoglobin and maternal and perinatal outcomes in a cohort of 1200 women, and to highlight the importance of antenatal care to improve maternal health, maternal and fetal outcome. Method All singleton pregnancies delivering at NKPSIMS, from January 2009 to December 2009 that fulfilled the required criteria were included. Results Out of 1200 women, 787 were anemic (67.2%) < 11 gm of Hb and 413 were nonanemic. Perinatal outcome included preterm delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…There was no neonatal deaths s in our study. Bakhtiar et al, 10 Lone FW et al, 11 Bhalerao A et al 12 reported low APGAR score at 1 min 1.7, 1.8, 1.8 times higher risk in anaemic mothers than non-anaemic mothers.…”
Section: Discussionmentioning
confidence: 97%
“…There was no neonatal deaths s in our study. Bakhtiar et al, 10 Lone FW et al, 11 Bhalerao A et al 12 reported low APGAR score at 1 min 1.7, 1.8, 1.8 times higher risk in anaemic mothers than non-anaemic mothers.…”
Section: Discussionmentioning
confidence: 97%